Glacier topography and elevation changes from Pléiades very high resolution stereo images - Berthier, E. (2014)
In response to climate change, most glaciers are losing mass and hence contribute to sea-level rise. Repeated and accurate mapping of their surface topography is required to estimate their mass balance and to extrapolate/calibrate sparse field glaciological measurements. In this study we evaluate the potential of Pléiades sub-meter stereo imagery to derive digital elevation models (DEMs) of glaciers and their elevation changes. Our five validation sites are located in Iceland, the European Alps, the Central Andes, Nepal and Antarctica. For all sites, nearly simultaneous field measurements were collected to evaluate the Pléiades DEMs. For Iceland, the Pléiades DEM is also 10 compared to a Lidar DEM. The vertical biases of the Pléiades DEMs are less than 1m if ground control points (GCPs) are used, but reach up to 6m without GCPs. Even without GCPs, vertical biases can be reduced to a few decimetres by horizontal and vertical co-registration of the DEMs to reference altimetric data on ice-free terrain. Around these biases, the vertical precision of the Pléiades DEMs is ±1m and even ±0.5m 15 on the flat glacier tongues (1-sigma confidence level). We also demonstrate the high potential of Pléiades DEMs for measuring seasonal, annual and multi-annual elevation changes with an accuracy of 1m or better. The negative glacier-wide mass balances of the Argentière Glacier and Mer de Glace (−1.21±0.16 and −1.19±0.16 m.w.e. yr−1, respectively) are revealed by differencing SPOT5 and Pléiades DEMs acquired in August 2003 and 2012 demonstrating the continuing rapid glacial wastage in the Mont-Blanc area.